Implicit emotion regulation in the presence of threat: Neural and autonomic correlates - Tupak, Sara V.; Dresler, Thomas; Guhn, Anne; Ehlis, Ann-Christine; Fallgatter, Andreas J.; Pauli, Paul; Herrmann, Martin J. (NeuroImage (Orlando, Fla.), 2014)
Efficient emotion regulation is essential for social interaction and functioning in human society and often happens without direct intention and conscious awareness. Cognitive labeling of stimuli based on certain characteristics has been assumed to represent an effective strategy of implicit emotional regulation whereas processing based on simple perceptual characteristics (e.g., matching) has not. Evidence exists that the ventrolateral prefrontal cortex (VLPFC) might be of functional relevance during labeling by down-regulating limbic activity in the presence of threatening stimuli. However, it remained unclear whether this VLPFC activation was particularly specific to threat because previous studies focused exclusively on threatening stimuli. In the current study, 35 healthy participants labeled or matched both threatening and neutral pictures while undergoing 52-channel functional near-infrared spectroscopy. Results showed increased VLPFC activation during labeling of threatening but not neutral pictures. No increase in prefrontal activation was detected during matching. Moreover, skin conductance increased equally for both valence conditions during initial phases of labeling whereas during matching stronger increases were found for threatening stimuli. Although a general inverse relationship between VLPFC function and skin conductance was not confirmed, both were negatively correlated during matching of threatening pictures in subjects with high state anxiety. It was concluded that the VLPFC plays an essential role during implicit emotion regulation. Further, even simple perceptual processing seems to engage regulatory top-down activation in anxious individuals. •Implicit emotion regulation activates the VLPFC.•The VLPFC is activated by cognitive but not perceptual evaluation of threat.•Perceptual processing alone activates emotional regulation in high anxious subjects.